2017
DOI: 10.1161/jaha.116.003620
|View full text |Cite
|
Sign up to set email alerts
|

Serum Acylcarnitines and Risk of Cardiovascular Death and Acute Myocardial Infarction in Patients With Stable Angina Pectoris

Abstract: BackgroundExcess levels of serum acylcarnitines, which are intermediate products in metabolism, have been observed in metabolic diseases such as type 2 diabetes mellitus. However, it is not known whether acylcarnitines may prospectively predict risk of cardiovascular death or acute myocardial infarction in patients with stable angina pectoris.Methods and ResultsThis study included 4164 patients (median age, 62 years; 72% men). Baseline serum acetyl‐, octanoyl‐, palmitoyl‐, propionyl‐, and (iso)valerylcarnitine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 47 publications
9
46
0
Order By: Relevance
“…Acylcarnitines are lipid intermediates that shuttle fatty acids into mitochondria for β-oxidation, [43] and several prior studies have demonstrated that impaired carnitine shuttle function and elevated acylcarnitine levels predict adverse cardiovascular outcomes and death in CAD patients. [44][45][46][47] We were able to validate these findings in our cohort in addition to other novel metabolites.…”
Section: Plos Onesupporting
confidence: 65%
“…Acylcarnitines are lipid intermediates that shuttle fatty acids into mitochondria for β-oxidation, [43] and several prior studies have demonstrated that impaired carnitine shuttle function and elevated acylcarnitine levels predict adverse cardiovascular outcomes and death in CAD patients. [44][45][46][47] We were able to validate these findings in our cohort in addition to other novel metabolites.…”
Section: Plos Onesupporting
confidence: 65%
“…In a mice model, Bodil and colleagues have reported an increase in plasma acylcarnitine levels caused by inhibition of mitochondrial fatty acid oxidation [ 42 ]. In clinical studies, elevated plasma acylcarnitine levels have been shown to be associated with age-related cardiometabolic conditions such as the risk of T2D and CVD, independently of age [ 43 46 ]. Notwithstanding these observations, other explanations are possible, and further studies are required to validate our findings.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent data, serum LCAC represents an independent risk factor of acute myocardial infarction in patients with angina pectoris, etc. [ 62 ]. Mitochondria isolated from ischemic areas of myocardium accumulate LCAC and respective long-chain acyl-CoA, which are known to suppress oxidative phosphorylation [ 15 ].…”
Section: Discussionmentioning
confidence: 99%